Device-measured physical activity and cardiovascular disease risk in adolescent childhood cancer survivors. A physical activity in childhood cancer survivors (PACCS) study - Mari Bratteteig; Sigmund Alfred Anderssen; Corina Silvia Rueegg; Ellen Ruud; Ellen Ruud; Ingrid Kristin Torsvik; Susi Kriemler; May Grydeland (Frontiers Media S.A., 2022)
ObjectivesWe aimed to compare cardiovascular disease (CVD) risk factors in childhood cancer survivors (CCS) with age- and sex-stratified reference material and examine the association between physical activity (PA) intensities and CVD risk factors in CCS.Materials and methodsWithin the cross-sectional, multicenter Physical Activity in Childhood Cancer Survivors (PACCS) study, we collected data on CVD risk factors [VO2-peak (mL⋅kg-1⋅min-1), body mass index (BMI, kg/m2), systolic blood pressure (SBP, mmHg), and total-cholesterol/HDL-cholesterol (Total/HDL)] among CCS aged 9-18 years. CVD risk factors were compared to references with immediate t-tests. We transformed CVD risk factors into z-scores based on international references and generated an individual CVD risk score: [inverse ZVO2-peak + ZBMI + ZSBP + ZTotal/HDL)/4]. Multivariable mixed linear regression models were used to analyze the associations between device-measured PA intensities and CVD risk factors.ResultsWe included 157 CCS aged on average 13.4 years at inclusion and 8.2 years from diagnosis. Male CCS had lower VO2-peak compared to references (45.4 vs. 49.4 mL⋅kg-1⋅min-1, P = 0.001), higher diastolic BP (67 vs. 63 mmHg, P < 0.001), lower HDL (1.35 vs. 1.44 mmol/L, P = 0.012), as well as a tendency to higher CVD risk score (z-score=0.14 vs. 0.00, P = .075). Female CCS' CVD risk factors were comparable to references. Vigorous-intensity PA (VPA) was associated with CVD risk factors. A 10-min increase in VPA was associated with higher VO2-peak (β = 4.9, 95% CI, 2.1-7.7), lower Total/HDL (β = −0.3, 95% CI, −0.6 to −0.1) and a lower CVD risk score (β = −0.4, 95% CI, −0.6 to −0.2).ConclusionMale adolescent CCS had less favorable values of CVD risk factors compared to references. VPA in adolescent CCS is associated with clinically meaningful favorable values of CVD risk factors.